Prefered Feed of Anoa (Bubalus sp.) at Manado Forestry Research Institute Captivity - Arini, Diah Irawati Dwi; Kafiar, Yermias (Jurnal Wasian, 2014)
The present study aims to determine the type of fodder available and the level of scarcity of Anoaâs fodder at the condition prior to captivity at the Forestry Research Institute of Manado. The method employed was a trial of 12 (twelve) types of fodder available around the captivity site given to 2 (two) female anoas. The data were analyzed and displayed in tables and graphs while the data of preferred fodder were analyzed using Neuâs index equation. The findings suggest that anoa put in captivity at the Forestry Research Institute of Manado did not encounter problems during the process of feeding adaptation. The average fodder needs required anoa at the captivity site ofÂ  the Forestry Research Institute of Manado range from 10.2 to 11.7 kg/ day in which the fodder was given twice a day. Meanwhile, based on the availability and ease of supplying the fodder from around the captivity site, the following are the types of fodder from higher to lower preferences, namely: field grass, kangkung, shoes banana, string beans, beans and cucumbers, respectively. While fodder with the lowest level of scarcity is the type of fodder with a hard texture such as sweet potatoes, carrots or potatoes. Based on the results of a number of studies, it is recommended that variations in anoaâs fodder can be done every 4-5 times a day.